2019
DOI: 10.30682/nm1903f
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency Estimation of Dairy Farming in Kosovo

Abstract: The aim of this research paper is to assess the technical efficiency (TE) of milk production in Kosovo using the stochastic frontier analysis. Research data are collected through surveys from 100 commercially oriented dairy farmers. The study finds that TE of milk production by most of these farms is high. Using the Cobb-Douglas production function, individual measures of TE range from 0.87 to 0.98 (on a scale of 0 to 1.00) with the average being 0.95. There were 57 farms with TE greater than 0.95 and 35 farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…Under the CRS model, the results of this study agree with the study of (Musliu et al, 2019) whose dairy farms used in their study resulted in mean TE of 0.95. Additionally, results show that 40% of sampled farms scored 1.000 both on CRS and VRS as well, thus are scale efficient.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Under the CRS model, the results of this study agree with the study of (Musliu et al, 2019) whose dairy farms used in their study resulted in mean TE of 0.95. Additionally, results show that 40% of sampled farms scored 1.000 both on CRS and VRS as well, thus are scale efficient.…”
Section: Resultssupporting
confidence: 87%
“…(Bajrami et al, 2017), found that in national level dairy farms in Kosovo scored 0.72 (on a scale 0-1.00) of Technical Efficiency. While in another study conducted by (Musliu et al, 2019), dairy farms in Kosovo had better results of TE, 0.95. However, there was no study specifically for dairy farms -beneficiaries of direct payments for milk quality.…”
Section: Introductionmentioning
confidence: 83%
“…The study results are consistent with other authors' studies performed earlier in the field of designing tools for dairy farming [12,[47][48][49][50][51] and complement them. An essential feature of this study methodology consists in the fact that the parameters affecting the efficiency of cleansing teats were taken into account as much as possible.…”
Section: Discussion Of the Results Obtained In Studying The Technical Means For Mechanical Cleansing Of Cow Udder Teatssupporting
confidence: 92%
“…These changes are expected to be reflected in a higher level of efficiency in the operation of the farms. Indeed, Musliu et al [40] estimated the technical efficiency of 57 farms in Kosovo using SFA and reported a high TE score of 0.95, a result that is in accordance with our findings. In addition, Náglová and Rudinskaya [18], based on panel data obtained from the Farm Accountancy Data Network (FADN) database covering EU member states (no data available for Cyprus and Greece) for 2004-2019, calculated an average TE score of 0.900 for EU-27 members.…”
Section: Efficiency Analysissupporting
confidence: 92%